Selection and inheritance of sexually dimorphic juvenile plumage coloration. Issue 22 (2nd November 2015) - Tringali, Angela; Bowman, Reed; Husby, Arild
Abstract: Sexually dimorphic plumage coloration is widespread in birds and is generally thought to be a result of sexual selection for more ornamented males. Although many studies find an association between coloration and fitness related traits, few of these simultaneously examine selection and inheritance. Theory predicts that sex‐linked genetic variation can facilitate the evolution of dimorphism, and some empirical work supports this, but we still know very little about the extent of sex linkage of sexually dimorphic traits. We used a longitudinal study on juvenile Florida scrub‐jays ( Aphelocoma coerulescens ) to estimate strength of selection and autosomal and Z‐linked heritability of mean brightness, UV chroma, and hue. Although plumage coloration signals dominance in juveniles, there was no indication that plumage coloration was related to whether or not an individual bred or its lifetime reproductive success. While mean brightness and UV chroma are moderately heritable, hue is not. There was no evidence for sex‐linked inheritance of any trait with most of the variation explained by maternal effects. The genetic correlation between the sexes was high and not significantly different from unity. These results indicate that evolution of sexual dimorphism in this species is constrained by low sex‐linked heritability and high intersexual genetic correlation. Abstract : Plumage color in juvenile Florida scrub‐jays shows relatively minor sexual dimorphism, and is moderately heritable with no evidence of sex‐linkage. We did not detect selection on plumage color, despite its use as a signal of dominance among juveniles.